A New Practical Route to ZSM‐5 Nanoparticles and Optimization of Synthetic Parameters through D‐optimal Design of Experiments. Issue 9 (27th August 2015) - Soltanali, Saeed; Halladj, Rouein; Rashidi, Alimorad; Bazmi, Mansour; Khodabakhshi, Saeed
Abstract A D‐optimal experimental design with three levels of SiO2/Al2O3, template/SiO2, H2O/SiO2, Na2O/SiO2 and TPABr/TPAOH ratio parameters has been used to optimize the experimental parameters by an analysis of variances (ANOVA). The effects of these ratios in the initial synthetic mixture on the size of the ZSM‐5 zeolite nanoparticles have been studied. XRD and FE‐SEM analyses were used to characterize synthetic samples. Fischer test results showed that H2O/SiO2 and TPABr/TPAOH ratios are the most and least effective parameters, respectively, in the range studied. The most important two‐way interaction variables were the interaction of template/SiO2 and TPABr/TPAOH molar ratios. The average particle size was in the 34–79 nm range. Furthermore, a mathematical model for the synthesis of ZSM‐5 zeolite nanoparticles was derived using experimental results. The optimized gel composition is as follows: SiO2/Al2O3=91.20, template/SiO2=0.16, H2O/SiO2=40.42, Na2O/SiO2=0.0147 and TPABr/TPAOH=0.